2002
DOI: 10.1057/palgrave/ejis/3000418
|View full text |Cite
|
Sign up to set email alerts
|

Vicious and virtuous cycles in ERP implementation: a case study of interrelations between critical success factors

Abstract: ERP Implementations are complex undertakings. Recent research has provided us with plausible critical success factors (CSFs) for such implementations. This article describes how one list of CSFs (Nelson and Somers 2001) was used to analyse and explain project perfonnance in one ERP implementation in the aviation industry. In this particular case, poor project performance led to a serious project crisis but this situation was tumed around into a success. The list of CSFs employed was found to be helpful and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 3 publications
3
111
0
4
Order By: Relevance
“…Early research into ERP implementation success factors (e.g., Holland and Light 1999, Jarrar et al 2000, Grabski et al 2001, Somers and Nelson 2001, Akkermans and van Helden 2002) generated lists of factors that contribute to successful ERP implementation. However, they did not indicate whether all the factors were needed, or if all the factors needed to be used with the same level of effort.…”
Section: Erp Success Factorsmentioning
confidence: 99%
“…Early research into ERP implementation success factors (e.g., Holland and Light 1999, Jarrar et al 2000, Grabski et al 2001, Somers and Nelson 2001, Akkermans and van Helden 2002) generated lists of factors that contribute to successful ERP implementation. However, they did not indicate whether all the factors were needed, or if all the factors needed to be used with the same level of effort.…”
Section: Erp Success Factorsmentioning
confidence: 99%
“…According to Staehr et al (2002), implementation research (e.g. Ng et al, 1999;Umble, Umble and Von Deylen, 2001;Weston, 2001;Akkermans and van Helden, 2002;Gefen, 2002;Abdinnour-Helm, Lengnick-Hall and Lengnick-Hall, 2003;Al-Mashari, Al-Mudimigh and Zairi, 2003;Craighead and LaForge, 2003;Mabert, Soni and Venkataramanan, 2003;Muscatello, Small and Chen, 2003;Schrnederjans and Kim, 2003;Somers and Nelson, 2003;Umble, Haft and Umble, 2003;Sheu, Chae and Yang, 2004) is the more developed of the two.…”
Section: Enterprise Resource Planning (Erp) Systemsmentioning
confidence: 99%
“…Hong and Kim (2002) reported that ERP implementation success substantially depends on the organizational fit of ERP and certain implementation contingencies. Akkermans and van Helden (2002) explained how one list of CSFs (Somers & Nelson, 2001) could be implemented to analyze and describe project performance in one ERP implementation in the aviation industry and reported that poor project performance could lead to a serious project crisis.…”
Section: Enterprise Resource Planningmentioning
confidence: 99%